Overexpression of TaMYC2 confers freeze tolerance by ICE-CBF-COR module in Arabidopsis thaliana - Wang, Rui; Yu, Mengmeng; Xia, Jingqiu; Xing, Jinpu; Fan, Xiaopei; Xu, Qinghua; Cang, Jing; Zhang, Da (Frontiers in Plant Science, 2022)
Dongnongdongmai No.1 (Dn1) is one of the few winter wheat varieties that can successfully overwinter at temperatures as low as -25°C or even lower. To date, few researches were carried to identify the freeze tolerance genes in Dn1 and applied them to improve plant resistance to extreme low temperatures. The basic helix-loop-helix (bHLH) transcription factor MYC2 is a master regulator in JA signaling, which has been reported to involve in responses to mild cold stress (2°C and 7°C). We hypothesized that MYC2 might be part of the regulatory network responsible for the tolerance of Dn1 to extreme freezing temperatures. In this study, we showed that wheat MYC2 (TaMYC2) was induced under both extreme low temperature (-10°C and-25°C) and JA treatments. The ICE-CBF-COR transcriptional cascade, an evolutionary conserved cold resistance pathway downstream of MYC2, was also activated in extreme low temperatures. We further showed that overexpression of any of the MYC2 genes from Dn1 TaMYC2A, B, D in Arabidopsis led to enhanced freeze tolerance. The TaMYC2 overexpression lines had less electrolyte leakage and lower malondialdehyde (MDA) content, and an increase in proline content, an increases antioxidant defences, and the enhanced expression of ICE-CBF-COR module under the freezing temperature. We further verified that TaMYC2 might function through physical interaction with TaICE41 and TaJAZ7, and that TaJAZ7 physically interacts with TaICE41. These results elucidate the molecular mechanism by which TaMYC2 regulates cold tolerance and lay the foundation for future studies to improve cold tolerance in plants.